Identidad y cultura corporativa del Servicio Ecuatoriano de Capacitación Profesional (SECAP) en las zonas 2 y 9: Quito y Galápagos - Montenegro Coba, Lorena Pamela (2015)
Today, communication has an important role within an organization, being the strategic key to position and make it competitive with the others. Several companies focus their actions in enhancing their external image first and then give importance to internal. This is the case of the Servicio Ecuatoriano de Capacitación Profesional, SECAP, a public institution under the Ministry of Labor Relations, which since 1966 has been its function professionally train and educate Ecuadorians. With 49 years in the Ecuadorian market, SECAP was part of the transformation that the Government launched in all state institutions. In the past two years, the institution has been transformed both processes and infrastructure, changing the image of an ancient institution to an institution at the forefront of the demands of society. However, internal communication problems observed, undermine the efficiency, productivity and attitude of officials, threatening to the new process of continuous improvement. The research project focuses specifically on Zones 2 and 9 (North of Quito, Quito Centre, South of Quito and Galapagos) SECAP; same as presented considerable shortcomings as far as internal communication is concerned. For this reason, it has made a situational study of areas indoors, listening to the needs of staff and feeling close the communication weaknesses to which they are exposed, later to make based on strategies and real actions to strengthen growth plan institutional.